DIGITAL MARKETING : STRATEGI PROMOSI APOTEK SAWOJAJAR MAS - Siti Indah Purwaning Yuwana (Reinforce: Journal of Sharia Management, 2022)
The rapid development of information technology has an impact on business activities ranging from small to large scale which requires utilizing sophistication in running their business. Innovative promotional strategies using the right media are needed to reach the market and increase sales volume. Digital Marketing is present as a marketing medium that is currently in great demand by all people. Sawojajar Mas Pharmacy is a business that sells medicines, foodstuffs and medical devices located in Malang City. The COVID-19 pandemic has limited visits to pharmacies, because it reduces physical contact with consumers. Of course this has a significant impact on sales turnover. To optimize sales volume, Sawojajar Mas Pharmacy utilizes online marketing and sales with various applications. This study aims to analyze how the promotion strategy carried out by Sawojajar Mas Pharmacy uses Digital Marketing to expand the market, increase sales turnover and attract new consumers. The research method in this study used a descriptive qualitative approach. Data collection uses 3 techniques, namely interviews, documentation and participant observation. Interviews were conducted with 3 informants who were appointed as resource persons. The results of the study explain that Sawojajar Mas Pharmacy as one of the pharmaceutical businesses in Malang City has succeeded in using Digital Marketing as an effective promotional tool, by utilizing social media, where its implementation provides enormous benefits for the company's marketing strategy.